REKAMAN STASIUN GPS SEBAGAI PENDETEKSI PERGERAKAN TEKTONIK, STUDI KASUS: BENCANA TSUNAMI ACEH 26 DESEMBER 2004 - Fajar Rizki Widiatmoko; Akhmad Zamroni; Muhammad Abdurrozak Siamashari; Afifah Nurul Maulina (Institut Teknologi Adhi Tama Surabaya, 2019)
Geographic Position System (GPS) is an electronic instrument that is used to determine the position of coordinates, with the help of the triangulation of satellite signals it can be accurately determined the coordinates of the position. An embedded GPS station is built to track changes in station positions over a period of time. Changes in position over a period of time are calculated using the GPS kinematic method and summed up simply using the GPS velocity method. International GNSS Service (IGS) is a global GPS data provider service with time-per-second densities and millimeter accuracy. During the Aceh tsunami tragedy 26 December 2004 00.58'.53